2016
DOI: 10.1111/chd.12435
|View full text |Cite
|
Sign up to set email alerts
|

Reducing variation in feeding newborns with congenital heart disease

Abstract: Implementation of experience-based newborn feeding guidelines for initiation and advancement of enteral feeding in the cardiothoracic intensive care unit was successful in reducing practice variation supported by increasing guideline compliance. Percentage of patient's full oral feeding at discharge did not change. Length of hospital stay was reduced although cannot be fully attributed to feeding guideline implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Some of the studies emphasize caloric delivery while others focus on standardization and decrease practice variation among providers. 8 One major difference compared with other prior studies such as Simsic et al 8 is every patient in our inclusion cohort underwent CPB. 8 Newcombe and Fry-Bowers 2 excluded patients with hemodynamic instability defined as patients on Milrinone infusions or inotropic drips.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some of the studies emphasize caloric delivery while others focus on standardization and decrease practice variation among providers. 8 One major difference compared with other prior studies such as Simsic et al 8 is every patient in our inclusion cohort underwent CPB. 8 Newcombe and Fry-Bowers 2 excluded patients with hemodynamic instability defined as patients on Milrinone infusions or inotropic drips.…”
Section: Discussionmentioning
confidence: 82%
“… 5 , 6 Studies have also shown patients receiving TPN have an increased risk of a central line–associated blood stram infections (CLABSI) and a reduction of time on TPN is beneficial to patients. 7 Adherence to a feeding protocol may decrease these risks and improve quality of care by reducing practice variation among providers.. 1 , 4 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another randomized study evaluated the use of human milk fortifier and described a trend in reduction in length of MV, ICULOS, and HLOS. A case control study evaluated the implementation of a feeding protocol for the initiation and advancement of enteral feeding in children with CHD and observed a reduction in HLOS after the implementation.…”
Section: Discussionmentioning
confidence: 99%
“…A future collaboration between the American and European societies might improve upcoming guidelines and help implement the recommendations worldwide. Despite these limitations, this work has provided an updated summary of the existing evidence, including questions around term neonates, which are not dealt with by other recommendations or guidelines, yet comprise a significant amount of the European PICU population [29,30].…”
Section: Limitationsmentioning
confidence: 99%